The concept of global monsoon applied to the last glacial maximum: A multi-model analysis. (15th October 2015) - Jiang, Dabang; Tian, Zhiping; Lang, Xianmei; Kageyama, Masa; Ramstein, Gilles
Abstract: The last glacial maximum (LGM, ca. 21, 000 years ago) has been extensively investigated for better understanding of past glacial climates. Global-scale monsoon changes, however, have not yet been determined. In this study, we examine global monsoon area (GMA) and precipitation (GMP) as well as GMP intensity (GMPI) at the LGM using the experiments of 17 climate models chosen from the Paleoclimate Modelling Intercomparison Project (PMIP) according to their ability to reproduce the present global monsoon climate. Compared to the reference period (referring to the present day, ca. 1985, for three atmospheric plus two atm–slab ocean models and the pre-industrial period, ca. 1750, for 12 fully coupled atmosphere–ocean or atmosphere–ocean–vegetation models), the LGM monsoon area increased over land and decreased over the oceans. The boreal land monsoon areas generally shifted southward, while the northern boundary of land monsoon areas retreated southward over southern Africa and South America. Both the LGM GMP and GMPI decreased in most of the models. The GMP decrease mainly resulted from the reduced monsoon precipitation over the oceans, while the GMPI decrease was derived from the weakened intensity of monsoon precipitation over land and the boreal ocean. Quantitatively, the LGM GMP deficit was due to, first, the GMA reduction and, second, the GMPI weakening. In response to the LGM large ice sheets and lower greenhouse gas concentrations in the atmosphere, the global surface and tropospheric temperatures cooled, the boreal summer meridional temperature gradient increased, and the summer land–sea thermal contrast at 40°S – 70°N decreased. These are the underlying dynamic mechanisms for the LGM monsoon changes. Qualitatively, simulations agree with reconstructions in all land monsoon areas except in the western part of northern Australia where disagreements occur and in South America and the southern part of southern Africa where there is uncertainty in reconstructions. Simulations do not support an inter-hemispheric anti-phasing of monsoon intensity change as suggested by proxy data. Highlights: The concept of global monsoon was applied to the LGM using PMIP simulations. The LGM boreal land monsoon areas shifted southward. Both the LGM global monsoon precipitation and its intensity decreased. The LGM global monsoon changes can be well explained by dynamics. A model–data comparison was performed over land monsoon areas.